Development of the Swimbladder Surfactant System and Biogenesis of Lysosome-Related Organelles Is Regulated by BLOS1 in Zebrafish. Issue 3 (1st March 2018) - Chen, Tianbing; Song, Guili; Yang, Huihui; Mao, Lin; Cui, Zongbin; Huang, Kaiyao
Abstract: Hermansky-Pudlak syndrome (HPS) is a human autosomal recessive disorder that is characterized by oculocutaneous albinism and a deficiency of the platelet storage pool resulting from defective biogenesis of lysosome-related organelles (LROs). To date, 10 HPS genes have been identified, three of which belong to the octamer complex BLOC-1 (biogenesis of lysosome-related organelles complex 1). One subunit of the BLOC-1 complex, BLOS1, also participates in the BLOC-1-related complex (BORC). Due to lethality at the early embryo stage in BLOS1 knockout mice, the function of BLOS1 in the above two complexes and whether it has a novel function are unclear. Here, we generated three zebrafish mutant lines with a BLOC-1 deficiency, in which melanin and silver pigment formation was attenuated as a result of mutation of bloc1s1, bloc1s2, and dtnbp1a, suggesting that they function in the same complex. In addition, mutations of bloc1s1 and bloc1s2 caused an accumulation of clusters of lysosomal vesicles at the posterior part of the tectum, representing a BORC-specific function in zebrafish. Moreover, bloc1s1 is highly expressed in the swimbladder during postembryonic stages and is required for positively regulating the expression of the genes, which is known to govern surfactant production and lung development in mammals. Our study identified BLOS1 as a crucial regulator of the surfactant system. Thus, the zebrafish swimbladder might be an easy system to screen and study genetic modifiers that control surfactant production and homeostasis.